When links build networks: brief history about the Antropocaos Group - Miceli, Jorge Eduardo; Castro, Mora; Diaz Cordova, Diego (AWARI, 2020)
The Antropocaos Group of the Universidad de Buenos Aires has been working on topics related to Social Network Analysis and other complexity algorithms for more than 20 years. This article reviews some of the team’s productions lines of work and the more frequent methodological choices. To this end, we outlined a brief history of our formation in the university cloisters, from the beginning of the 1990s to the present day. We emphasize the empirical topics addressed by the group, in order to highlight both the conceptual variability and the methodological unity regarding different areas of Social Network Analysis application. A section is dedicated specifically to those studies where we implemented simulation models and the possibility to observe reticular phenomena in a controlled computational environment. The next section shows different areas in which the members of Antropocaos currently carry out their activities and apply reticular methods, including academic research, management, and public administration, and different sorts of consultancies. Finally, we point toward some guidelines about the future of the group, as well as the lines of research that are just being started, related to algorithms of Artificial Intelligence, as well as our long-standing commitment to disseminate the Social Networks Analysis methodology.